UNDERSTANDING OF ISLAM REPRODUCTION AS MUHAMMADIYAH'S DAKWAH MOVEMENT - ithriyah, Siti; Nurmawati, Nurmawati (Devotion : Journal of Research and Community Service, 2021)
Adolescence is a period of mental turmoil, a period of transition or on a rocking bridge, which connects dependent childhood with mature and independent adulthood. This situation shows how teenagers need help to solve the reproductive health problems they face through making the right decisions so they don't harm themselves or their future. One of the efforts that can be done to help adolescents solve the reproductive health problems they face is through understanding reproductive knowledge. Adolescent reproductive health information services aim to assist adolescents by exploring the conditions and problems they face, so that adolescents are able to make the right decisions in solving problems and what they see around them. The research method used is the method of preparation and implementation. The results of this study indicate that the implementation of the implementing team conducted a pre-test to students in order to make it easier for the implementing team to carry out the material to be conveyed through analysis and basic knowledge to students then the implementing team delivered the material and had a question and answer session and then students who wanted to consult about the problems experienced, students are allowed to come to the implementation team post or ask for the implementing team's phone number.